A multi-organ, feto-maternal interface organ-on-chip, models pregnancy pathology and is a useful preclinical extracellular vesicle drug trial platform - Melody Safarzadeh; Lauren S. Richardson; Ananth Kumar Kammala; Angela Mosebarger; Mohamed Bettayeb; Sungjin Kim; Po Yi Lam; Enkhtuya Radnaa; Arum Han; Ramkumar Menon (Extracellular Vesicle)
Pregnant women and their fetuses are often excluded from clinical trials due to missing drug-related pre-clinical trial information at the human feto-maternal interface (FMi). The two interfaces-placenta/decidua and fetal membranes/decidua are gatekeepers of drug transport; however, testing their functions is impractical during pregnancy. Limitations of current in-vivo/in-vitro models have hampered drug development and testing during pregnancy. Hence, major complications like preterm births and maternal and neonatal mortalities remain high. Advancements in organ-on-chip (OOC) platforms to test drug kinetics and efficacy and novel extracellular vesicle-based fetal drug delivery are expected to accelerate preclinical trials related to pregnancy complications. Here we report the development and testing of a humanized multi-organ fetal membrane/placenta (fetal)-decidua (maternal) interface OOC (FMi-PLA-OOC) that contains seven cell types interconnected through microchannels to maintain intercellular interactions as seen in-utero. Cytotoxicity, propagation, mechanism of action, and efficacy of engineered extracellular vesicles containing anti-inflammatory interleukin (IL)-10 (eIL-10) were evaluated to reduce FMi inflammation associated with preterm birth. A healthy and disease model (lipopolysaccharide-infectious inflammation) of the FMi-PLA-OOC was created and co-treated with eIL-10. eIL-10 propagated from the maternal to fetal side within 72-h, localized in all cell types, showed no cytotoxicity, activated IL-10 signaling pathways, and reduced lipopolysaccharide-induced inflammation (minimized NF-kB activation and proinflammatory cytokine production). These data recapitulated eIL-10s’ ability to reduce inflammation and delay infection-associated preterm birth in mouse models, suggesting FMi-PLA-OOC as an alternative approach to using animal models. Additionally, we report the utility of eIL-10 that can traverse through FMis to reduce inflammation-associated pregnancy complications.